Precision Rescue Behavior in North American Ants - Katherine Taylor; Allison Visvader; Elise Nowbahari; Karen L. Hollis (Evolutionary Psychology, 2013)
Altruistic behavior, in which one individual provides aid to another at some cost to itself, is well documented. However, some species engage in a form of altruism, called rescue, that places the altruist in immediate danger. Here we investigate one such example, namely rescuing victims captured by predators. In a field experiment with two North American ant species, Tetramorium sp. E and Prenolepis imparis, individuals were held in artificial snares simulating capture. T. sp. E, but not P. imparis, exhibited digging, pulling, and snare biting, the latter precisely targeted to the object binding the victim. These results are the first to document precision rescue in a North American ant species; moreover, unlike rescue in other ants, T. sp. E rescues conspecifics from different colonies, mirroring their atypical social behavior, namely the lack of aggression between non-nestmate (heterocolonial) conspecifics. In a second, observational study designed to demonstrate rescue from an actual predator, T. sp. E victims were dropped into an antlion's pit and the behavior of a single rescuer was observed. Results showed that T. sp. E not only attempted to release the victim, but also risked attacking the predator, suggesting that precision rescue may play an important role in this species' antipredator behavior.